Character education as the foundation of vocational curriculum: a case study at SMK Mardhotullah Al-Islamy - Eko Ngabdul Shodikin; Shafira Azzahra; Muhammad Zaki Tamami (At Turots: Jurnal Pendidikan Islam, 2024)
Character education has become a major focus in the education system in Indonesia, particularly in vocational schools. This study examines the integration of character education into the vocational curriculum at SMK Mardhotullah Al-Islamy, aiming to assess the impact of implementing the Panca Jiwa and Panca Karakter values on shaping students' character, balancing technical competence and moral integrity. This research uses a qualitative approach with a case study method. Data were collected through interviews with teachers, field observations, and analysis of curriculum documents and program implementation. Data analysis was conducted descriptively to describe the implementation and impact of character education in the vocational school context. The results show that the integration of character education into the vocational curriculum at SMK Mardhotullah Al-Islamy has successfully shaped students who are not only technically competent but also possess high moral values. The role of teachers as Ruhul Mudarris and the supportive school environment contributed significantly to the success of the program. Challenges encountered in the implementation of the program include time constraints, varying levels of understanding among teachers, and the socio-economic backgrounds of students. This study recommends that this approach be adapted by other vocational schools in Indonesia, with adjustments to local contexts